Hydraulic vs. Electric: A Comparative Review of Brake and Clutch Actuation Systems - Nitin Pal (International Journal of Machine Systems and Manufacturing Technology, 2024)
This review article compares hydro and electric actuation systems for clutches and brakes in detail, examining their design concepts, characteristics, and probable uses. Long-used in the automotive sector, hydraulic appliances use fluid pressure transmission to function. They are dependable and easy to use, but they have drawbacks such fluid leaks and complicated systems. On the other hand, electromechanical actuators serve their purpose in electric actuation systems, which provide benefits including accurate control, quicker reaction times, and integration with car electronics. However, there are issues with electric systems, such cost, heat management, and consistency. In along with analyzing technical breakthroughs and future possibilities, the comparative study covers specifications like performance, efficiency, dependability, cost, and adaptability. Electric systems have more efficiency and integration potential than hydraulic systems, despite hydraulic systems' superior dependability. The intricate interplay of variables influencing picking between these systems and the continuous evolution impacting vehicle braking and clutch control are highlighted in the final section of the paper.
Keywords: Hydraulic actuation systems; brake by wire systems; clutch engagement; electric actuation systems; integrated brake control